Growth of carbon nanotubes over carbon nanofibers catalyzed by bimetallic alloy nanoparticles as a bifunctional electrode for Zn–air batteries. Issue 17 (13th April 2023) - Aziz, Iram; Chen, Xing; Hu, Xuhui; (Angela) Zhang, Wenjing; Awan, Rabiya Javed; Rauf, Ali; Arshad, Salman Noshear
Abstract : In situ formed bimetallic nanoparticles aided the growth of CNTs over CNFs for enhanced oxygen reduction and evolution reactions in ZABs. Abstract : Design of economical, large-scale, stable, and highly active bifunctional electrocatalysts for Zn–air batteries with enhanced oxygen reduction and oxygen evolution performance is needed. Herein, a series of electrocatalysts were facilely fabricated where in situ formed bimetallic nanoparticles aided in the growth of carbon nanotubes over carbon nanofibers (MM'-CNT@CNF) during thermal treatment. Different combinations of Fe, Ni, Co and Mn metals and melamine as precursor for CNT growth were investigated. The synergistic interaction between bimetallic nanoparticles and N-doped carbon results in greatly improved bifunctional catalytic activity for both oxygen reduction and evolution reactions (ORR, OER) using FeNi-CNT@CNF as catalyst. The half-wave potential (0.80 V vs. RHE) for FeNi-CNT@CNF for ORR was close to that of Pt/C (0.79 V vs. RHE), meanwhile its stability was superior to Pt/C. Likewise, during OER, the FeNi-CNT@CNF reached a current density of 10 mA cm −2 at a rather low overpotential of 310 mV vs. RHE compared to benchmark RuO2 (410 mV). The rechargeable Zn-air prototype battery using FeNi-CNT@CNF as an air electrode outperformed the mixture of Pt/C and RuO2 with discharge/charge overpotential of 0.61 V, power density of 118 mW cm −2 at 10 mA cm −2 and an improved cycling stability over 108 hours.